Control y tratamiento de la tuberculosis en el Perú - Vargas Machuca, Ramon (2024)
The analysis of epidemiological indices in Peru, indicates that tuberculosis is a Public Health problem. Given the simplicity of tuberculosis control techniques, programmes could be developed to form an integral part of the Public Health Servide, thereby protecting a large percentage of the population nithout increasing of costs invelved.  Expensive chemotherapeutic regimens for tuberculosis are effective and would be suitable for use in private practice. Fortunately, there are low costs regimens of low toxicity and high efficacy that can be standardized an applied on a country widw and permanent basis.  According to the observation of the former tuberculosis dispensaries, now Health Centers, the results with the patients who took the drugs regularly were favourable in over 93%  of the cases. Nevertheless the failure to attend for treatment has a serious effect on these exellent results.  If an integrated national programme of sufficient quality would be developed the instances in which patients fail to continue to attend for treatment would diminish.